Providing BCP Trash Holder Near the Gate for Proper Waste Management in selected Grade 12 Accountancy, Business and Management Strand Students in Bestlink College of the Philippines, S.Y. 2019–2020 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research was focused on providing a BCP trash holder near the gate for proper waste management. The study revealed the aspects thatmay lead to an organized and good environment at the Bestlink College of the Philippines. A qualitative method was used in this study by using a descriptive research design. This study involved 50 selected Grade 12 Accountancy, Business, and Management Strand students. Three variables, such as students’ discipline, school management, and teachers’ moods, were considered. Improper waste disposal is one of the factors that affect the academic performance of students. Another aspect revealed that students may also be affected if they do not have discipline in throwing their garbage in appropriate trash bins. The study revealed that improper waste disposal has an impact on the academic performance of students. The study also showed that students have priority problems in their personal lives and school.
Keywords: improper waste disposal, proper waste management, students’ discipline, school management, teachers’ mood